Observation of the Υ(1 3 D J ) bottomonium state through decays to π + π − Υ(1S) - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
Based on 122×106Υ(3S) events collected with the BABAR detector, we have observed the Υ(13DJ) bottomonium state through the Υ(3S)→γγΥ(13DJ)→γγπ+π−Υ(1S) decay chain. The significance for the J=2 member of the Υ(13DJ) triplet is 5.8 standard deviations including systematic uncertainties. The mass of the J=2 state is determined to be 10 164.5±0.8(stat)±0.5(syst) MeV/c2. We use the π+π− invariant mass distribution to confirm the consistency of the observed state with the orbital angular momentum assignment of the Υ(13DJ).
Im Titel ist die Zahl "3" hochgestellt und der Buchstabe "J" tiefgestellt. Plus- und das Minuszeichen sind hochgestellt
BABAR Collaboration: P. del Amo Sanchez, A. Adametz, J. Marks, S. Schenk, U. Uwer, T. Hartmann, T. Leddig, H. Schröder, R. Waldi [und viele weitere]
Gesehen am 23.08.2023